Dielectric Lens Antennas - Fernandes, C. A.; Lima, E. B.; Costa, J. R. (Handbook of Antenna Technologies, 2016)
Dielectric lens antennas are attracting a renewed interest for millimeter- and submillimeter-wave applications where they become compact, especially for configurations with integrated feeds usually referred as integrated lens antennas. Lenses are very flexible and simple to design and fabricate, being a reliable alternative at these frequencies to reflector antennas. Lens target output can range from a simple collimated beam (increasing the feed directivity) to more complex multi-objective specifications. This chapter presents a review of different types of dielectric lens antennas and lens design methods. Representative lens antenna design examples are described in detail, with emphasis on homogeneous integrated lenses. A review of the different lens analysis methods is performed, followed by the discussion of relevant lens antenna implementation issues like feeding options, dielectric material characteristics, fabrication methods, and a few dedicated measurement techniques. The chapter ends with a detailed presentation of some recent application examples involving dielectric lens antennas.